Development and applications of the single-case design risk of bias tool for evaluating single-case design research study reports. (August 2018) - Reichow, Brian; Barton, Erin E.; Maggin, Daniel M.
Highlights: A new method for evaluating risk of bias for single-case design studies is proposed. Two illustrative examples of the method's application are presented. This new method provides a mechanism to review similar risks of bias in group and single-case design research within the same review. Abstract: Systematic reviews and meta-analyses can be a useful method for synthesizing evidence across multiple studies to draw conclusions about a research base. An important aspect of rigorous systematic reviews is an assessment of the study methods and potential biases impacting results or interpretations and conclusions of the primary studies. Single-case design (SCD) research has been a primary mechanism for identifying evidence-based practices across disciplines, but primarily in behavioral fields and special education. While the Cochrane Risk of Bias tool has been adapted for use in reviews of non-randomized studies, there is currently no guidance for evaluating SCD research. Hence, we developed a single case design risk of bias tool (SCD RoB) based on current conceptualizations of biases that might affect the validity of claims from single-case design research. We used the Cochrane risk of bias criteria and contemporary single-case design quality indicators and design standards to guide development. We describe the SCD RoB tool and two early applications of its use to demonstrate its application and provide initial validation. We also provide an overview of future areas of research using the SCD RoB tool in an effort to advance the science of single-case design research methods.